Legal Analysis of the Application of Criminal Sanctions Against Perpetrators of Aggravated Theft Based on Pancasila Justice (Criminal Case Study Decision Number: 170/Pid.B/2024/PN.Skt) - Sutadharma, Putu Andy; Bawono, Bambang Tri (Jurnal Hukum Khaira Ummah, 2025)
The background of the problem began with the rampant corruption cases in the Village Credit Institutions (LPD) in Bali. LPD management that deviates from the provisions of laws and regulations is prosecuted as a criminal act of corruption. The dilemma in imposing a replacement fine on LPD corruption cases in Bali is interesting to study further. If the replacement money is paid to the State Treasury, the state's loss in this case the LPD's loss is irrecoverable. Several judges' decisions impose a replacement fine with the order that reads "Ordering the defendant to pay the replacement money to the State Treasury cq LPD". The implementation of the replacement fine is open to multiple interpretations and tends not to side with the community/krama who are victims of the corruption. This study uses a normative legal research method. The results of this study aim to solve the issue of criminalizing replacement money for corruption crimes that occurred at LPD in Bali from the perspective of state losses, in this case LPD losses, where the victims are LPD customers/krama. That there are still many other similar decisions that include the injunction, namely imposing a replacement monetary penalty that is deposited into the State Treasury cq. LPD Cash. It is implied that the purpose of the replacement monetary penalty from the verdict which states that it is deposited into the State Treasury cq. LPD Cash is intended to recover state losses in this case suffered by the community as LPD customers themselves. It appears that the regulation of replacement monetary penalties as stipulated in Article 18 paragraph (1) letter b for defendants in the perspective of corruption crimes in LPD in Bali, the legal norms are vague or unclear (unclear of norm/vague van de normen). The solution to this unclear legal norm requires interpretation or interpretation for law enforcers, especially judges, in imposing additional criminal sentences whose purpose is to replace state losses in this case LPD losses.